Brazilian Literature on Ayahuasca Religions - Labate, Beatriz Caiuby (Fieldwork in religion, 2006)
The purpose of this text is to provide an overview of Brazilian literature on the principal ayahuasca religions of Brazil: Santo Daime, the Barquinha and the União do Vegetal. To this end, the article offers the most exhaustive survey available of the university theses that have been produced on the subject, published or not; it also deals with various research projects in progress and a few articles which have been chosen for their particular importance. Beyond that, we shall comment on several works of a non-academic nature produced by adepts of ayahuasca religions. This effort to provide an overview of the whole area is especially important since the majority of the studies about the topic are scattered, many of them have not been published and are difficult to obtain. The article is organized in two parts. The first part comments on the academic works. Generally speaking, the anthropological works deal with the uses of ayahuasca from the point of view of beliefs and symbolic systems, touching particularly on topics such as syncretism, shamanism, and healing.